Peningkatan Literasi Struktural Melalui Pendampingan Teknis Analisis Struktur pada Pembangunan Gedung NU di Desa Kalisoka Kab Tegal - Weimintoro Weimintoro,; Nadya Shafira Salsabilla,; Teguh Haris Santoso,; Ahmad Farid,; Agus Wibowo, (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2026)
Community service activities were carried out by a team of lecturers from Pancasakti University Tegal. The goal is to apply civil engineering science to analyze and plan the structure of the Nahdlatul Ulama (NU) Building located in Kalisoka Village, Tegal Regency. The main objective of this activity is to ensure that the design of the building meets national standards in terms of strength, rigidity, and resistance to earthquake loads. To achieve this goal, the team used several methods such as surveys in the field, determining the structure of the building, analyzing the accepted loads, and modeling the structure with SAP2000 software. The calculation of reinforced concrete elements refers to SNI 2847:2019 and SNI 1726:2019. The results of the analysis showed that the size of the structure and the requirements of reinforcement were in accordance with the factors of safety and material efficiency. This activity shows the important role of universities in supporting the development of public infrastructure that is safe, economical, and in accordance with national technical standards through the application of science directly in the community. In addition, the results of this activity are expected to be an example of the application of structural engineering technology based on national standards in other construction projects in rural areas, so that the quality of development can be improved sustainably.